Tingkat Keberhasilan Kinerja Penyuluh dalam Meningkatkan Sumberdaya Petani Padi Sawah di Desa Tanah Poleang, Kecamatan Poleang Utara - Sukmawati Abdullah; Suriana; Yoenita Jayadisastra; Bunyamin; Anjasmara (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2023)
This research was carried out from August to December 2021 in Tanah Poleang Village, North Poleang District, Bombana Regency and the location selection was determined purposively (purposive). This study aims to analyze the performance of extension workers and the level of success of extension workers in increasing the resources of lowland rice farmers. This study uses quantitative methods with the support of qualitative descriptive analysis data. The results showed that the performance of extension workers in increasing the resources of paddy rice farmers in Tanah Poleang Village was good in terms of responsiveness (56.25%), responsibility (59.38%), accountability (46.88%), and quality of service (50. 00%.) as a whole is in the medium category. The success rate of the performance of extension agents in increasing the resources of paddy rice farmers in Tanah Poleang Village based on the knowledge, attitudes and skills of farmers shows that each produces a percentage in each category for farmer knowledge getting a value of 53.13% in the high category, farmers' attitudes get a value 40.6% in the medium category and based on the skill of the farmer getting a score of 50.00% in the medium category.